رياضة الفروسية في الجزائر بين الفلكلور والاستخدامات العسكرية خلال الفترة الوسيطة - بن عمر, علال (جامعة الوادي - University of Eloued, 2023)
عرف إنسان المغرب الأوسط الخيول منذ العصور القديمة، فقد اهتم النوميديون بتربيتها واستغلالها في أغراض عدة؛ كالتنقلات والصيد والحرب، وعلى ذلك اشتهرت رياضة الفروسية بمكانة كبيرة لدى النوميديين، ومع قدوم العرب الفاتحين إلى بلاد المغرب في منتصف القرن السابع للميلاد؛ انتشرت الخيول العربية في المنطقة وتزايد أعدادها، وساهمت في حركة الفتح ويسرت للفاتحين طريق الدخول لبلاد المغرب. وسنحاول في هذه الورقة البحثية التعريج على أهمية الخيول بالنسبة لساكنة المغرب الأوسط ومدى استخدام أهل المغرب الأوسط للخيول في الحياة العامة العسكرية منها والاجتماعية والاحتفالات الدينية، وقد وقفنا على استخدام الخيول في السباقات الرياضية والفلكلورية، وتطرقنا لرياضة سباق الخيل ومدى اهتمام دول المغرب الأوسط بها بدءا من الرستميين ثم الحماديين وحتى الزيانيين، وبينا علاقة تلك الرياضة بتقاليد المنطقة وحضورها في احتفالات الختان واحتفالات المولد النبوي الشريف وغيرها. واعتمدنا المنهج التاريخي القائم على الوصف والتحليل والاستنتاج، أما عن إشكالية البحث فقد تمحورت حول علاقة إنسان المغرب الأوسط بالفروسية وركوب الخيل، وكيف أحسن أهل المغرب الأوسط استخدام الفروسية في مجالات متعددة تلبية لحاجياتهم المختلفة؟. وكان اعتمادنا في ذلك على عديد المصادر التاريخية أهمها ابن خلدون وكتابه العبر وابن عذارى المراكشي وكتابه البيان المغرب، والجغرافية أهمها صورة الارض لابن حوقل والمسالك للبكري . Abstract: The people of the Middle Maghreb have known horses since ancient times, as the Numidians were interested in breeding and exploiting them for several purposes, such as transportation, hunting and war. Thus, equestrian sport was renowned for its great place among the Numidians, and with the arrival of the conquerors in the Maghreb in the mid-seventh century, Arab horses have proliferated in the region and their numbers have increased, contributing to the conquest movement and facilitating the conquerors’ route into the Maghreb. In this paper, we will try to elaborate on the importance of horses for Maghreb’s central inhabitants and the extent to which the people of Maghreb use horses in military and social public life and religious ceremonies. We will address the use of horses in sports and folkloric racing. We will also tackle horse racing and the interest of the Central Maghreb States in it, including the Rustamids, Hammadis, and Zayyanids. We will demonstrate that sport’s relationship with the traditions of the region and its presence at Circumcision and the celebrations of the birth of the Prophet. The problem of the article will be about Maghreb’s relationship with equestrians and rides, and how did the people of Maghreb use equestrians in multiple areas to meet their different needs. We will rely on many historical sources, the most important of which are: Ibn Khaldun and his book Al-Ibar, Ibn Adhara Al-Marrakchi and his book Al-Bayan Al-Maghrib, geography the most important image of the land by Ibn Hawqal, the paths by Al-Bakri, and Al-Hassan Al-Wazzan in his book Description of Africa.
مقال
Keywords: الجزائر، فروسية، رياضة، تاريخ، فلكلور; Algeria, sports, equestrian, folklore,. History